The Design of Classroom Facilities in Primary Schools of Sumenep Regency for Improving Learning Effectiveness - Haney, Achmad; Zainuddin, Zainuddin; Kuswandi , Iwan (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2025)
This study examines the classroom facility design in outstanding public and private elementary schools in Sumenep Regency, Indonesia, to describe the management of classroom resources that impact student effectiveness, engagement, and creativity during the learning process. Using a descriptive qualitative method with a multi-case study design, data were collected through observation, documentation, and interviews with teachers and school principals. Data analysis followed Miles and Huberman's model of data reduction, display, and conclusion drawing. The results reveal that three of the five schools studied provided comprehensive literacy facilities and diverse thematic classrooms tailored to grade levels, while two had more basic facilities. Classroom arrangements differed between the lower and upper grades, with the upper classes featuring more structured resources that supported independent learning. These findings underscore the importance of adaptive classroom design in enhancing student learning success within the local context of Sumenep Regency. The study's findings offer valuable insights for educators and policymakers seeking to improve elementary school facilities.